The long journey towards Pan-African integration: The African Continental Free Trade Area and its challenges - Bernhard Tröster; Eva Janechová (Austrian Foundation for Development Research (ÖFSE), 2021)
On the 1st of January 2021, African countries started the African Continental Free Trade Area (AfCFTA). It is a largely symbolic step toward the long-term goal of economic integration on the African continent. The integration process includes an extensive agenda that requires time and will affect the development in African countries in multiple ways. While studies typically report potential trade and welfare gains, the overall impact of the agreement depends on various factors. In this ÖFSE Briefing Paper, we (i) present the state of play in the AfCFTA negotiations and implementation, (ii) discuss the challenges for the AfCFTA based on the characteristics of African trade, and (iii) offer a critical assessment of economic impact studies. A positive contribution of the AfCFTA to the Agenda 2063 of the African Union requires appropriate policies to overcome the limitations and challenges of the integration process, in particular through coordinated industrial policies. These efforts should be supported by the European Union, including through adjustments to its current trade regime with African partners.
Keywords: 330; AfCFTA; trade liberalization; continental integration; Regional EconomicCommunities; Economic Partnership Agreements